Integrating Leading and Lagging Areas : A Strategy for Making Prosperity for All a Reality - World Bank (Washington, DC, 2017)
Uganda's fast growth, which has averaged more than 7 percent during the past two decades, has helped reduce poverty the proportion of people living in poverty in the early 1990s has declined to less than half, from 56 percent to 24.5 percent by 2010. However, the reduction in poverty was uneven, and in some cases, poverty increased and inequality persists between and within regions. Partly driven by the uneven reduction in poverty, persistent inequality, and rising unemployment, Ugandan authorities have raised concern about the inclusiveness of Uganda's development. New programs, including prosperity for all, are being undertaken by the government to raise the incomes of households and, hence, close the income gap. Many developing countries are facing the same challenge of reducing spatial differences in living standards. The structural transformation that takes place as countries grow from low to high incomes is accompanied with prosperity in a few places, as has been observed from the history of many developed countries, and is being repeated in many developing ones, such as China, India, Indonesia, and Sri Lanka. This note is organized into six sections. Section two outlines the geography of living standards. Section three describes the transformation that has already happened in the geography of production and how it relates to the geography of living standards. Section four analyzes how the fluidity of two important markets in labor and land should contribute to Uganda's transformation and where the constraints to increased fluidity could be. A strategy for connecting people to prosperity is presented in section five. And finally, section six concludes with the summary of recommendations.